High Rate of Pulmonary Cement Embolism after Cement-Augmented Pedicle Screw Fixation: A 12-Year Single-Center Study - Lenga, Pavlina; Bajwa, Awais Akbar; Schneider, Till; Iwanaga, Joe; Tubbs, R. Shane; Kiening, Karl L.; Unterberg, Andreas W.; Ishak, Basem (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background The global trend toward increased life expectancy because of remarkable improvements in health care quality has drawn increased attention to osteoporotic fractures and degenerative spine diseases. Cement-augmented pedicle screw fixation has been established as the mainstay treatment for patients with poor bone quality. This study aimed to determine the number of patients with cement leakage and pulmonary cement embolism (PCE) as detected on thoracic computed tomography (CT), and to assess the potential risk factors for PCE.Methods Patients undergoing cement-augmented pedicle screw placement in our institution between May 2008 and December 2020 were included. Data regarding baseline characteristics, complications, and cement leakage rates were collected. Indications for the performance of a postoperative thoracic CT due to the suspicion of PCE were intra- or postoperative complications, or postoperative oxygen supplementation. Moreover, PCE was accidently diagnosed because the thoracic CT was performed for medical reasons other than the suspicion of PCE (tumor staging, severe pneumonia, or exacerbated chronic pulmonary obstructive disease).Results A total of 104 patients with a mean age of 72.8 years (standard deviation of 6.7) were included. Of 802 screws, 573 were cement augmented. Of the 104 patients, 44 (42.3%) underwent thoracic CT scans to diagnose PCE; additionally, 67 (64.4%) demonstrated cement leakage, of whom 27 developed PCE and 4 were symptomatic. Cement-augmented thoracic screws were a risk factor for PCE (odds ratio: 1.5; 95% confidence interval: 1.2–2.1; p = 0.004).Conclusions This study showed a high prevalence of cement leakage after cement-augmented pedicle screw insertion, with a relatively frequent incidence of PCE, as tracked by thoracic CT scans. Cement-augmented thoracic screw placement was a unique risk factor for PCE.
Keywords: cement leakage; cement-augmented pedicle screw placement; pulmonary cement embolism; osteoporotic fractures